Evolution and plasticity of Trinidadian guppies in the field, the laboratory, and the classroom - Broder, Emily Dale, author; Angeloni, Lisa M., advisor; Ghalambor, Cameron K., committee member; Hoke, Kim L., committee member; Whittemyer, George, committee member (Colorado State University. Libraries, 2016)
A fundamental question in evolutionary biology is how organisms respond to new and changing environments. This question also has conservation implications in the face of human induced rapid environmental change, including invasive species, habitat loss, and climate change. In response to new or changing environments, populations may evolve genetic changes across generations, and individuals may also respond via phenotypic plasticity within a generation. We can use experimental methods and model systems to increase our understanding of the way that genes and the environment interact to shape phenotypes. The Trinidadian guppy is a small freshwater fish that exhibits phenotypic plasticity as well as rapid evolution in response to changes in the environment, namely changes in the predator community. We utilized experimental introductions and common garden experiments to investigate plasticity and evolution of cerebral laterality, genitalia, and mating behavior in guppies. Predation pressure is thought to select for a higher degree of cerebral laterality, or consistency in the partitioning of tasks between hemispheres of the brain. However, we found no difference in laterality between populations that evolved with high versus low levels of predation in the wild (Chapter 1). Instead, brothers reared with chemical predator cues were more highly lateralized than their brothers reared without cues, which is likely adaptive plasticity since a higher degree of laterality is associated with enhanced antipredator behavior. This study revealed the important but largely overlooked role of developmental plasticity in shaping cerebral laterality. Next, we took advantage of an experimental introduction of guppies from an environment with many predators to four replicate streams that contained few predators. In only 4-8 guppy generations, males in the introduced populations evolved shorter gonopodia for a given body size compared to the source population with high predation risk (Chapter 2). This suggests that longer gonopodia are advantageous in environments with predators, consistent with the hypothesis that longer genitalia facilitate forced copulations and allow males to circumvent female choice. We also measured male mating behavior using the same experimental introduction. In approximately 8-12 generations, we documented evolutionary changes in several mating behaviors, but these patterns were not consistent across populations (Chapter 3). We also found that low food levels during development reduced mating effort, but we found no evidence of developmental plasticity in response to predator cues in the rearing environment. Instead, we found an important role for contextual plasticity, a reversible and rapid response to the current situation, evident in behavioral changes with acute chemical cues of predation. Contextual plasticity is though to be especially important for behavioral traits allowing flexibility in response to rapidly changing conditions. This represents one of the few empirical studies designed to explore evolution, developmental plasticity, and contextual plasticity in the same experiment. The Trinidadian guppy is also a model system for science education, with locally adapted populations that provide an accessible example of evolution by natural selection. We created a hands-on authentic science program with live guppy experiments to teach evolution to middle school students (Chapter 4). Authentic science allows students to discover knowledge by conducting science as if they were practicing scientists, which should be particularly effective at teaching evolution, yet few programs have been developed. Students who participated in our program exhibited significant increases in both knowledge and acceptance of evolution. Our work with Trinidadian guppies documented patterns of evolution and plasticity in new environments for a series of traits using a powerful experimental framework. These experiments revealed a role for both genes and the environment in the way predation risk shapes cerebral laterality, genitalia, and mating behavior, suggesting that the relationship between plasticity and evolution is complex and likely depends on the trait being studied. We also demonstrated how the guppy system, and other organisms that exhibit local adaptation, can be used to develop engaging and effective authentic science programs to teach evolution to K-12 students.